2021
DOI: 10.1371/journal.pntd.0009052
|View full text |Cite
|
Sign up to set email alerts
|

Impaired host resistance to Salmonella during helminth co-infection is restored by anthelmintic treatment prior to bacterial challenge

Abstract: Intestinal helminth infection can impair host resistance to co-infection with enteric bacterial pathogens. However, it is not known whether helminth drug-clearance can restore host resistance to bacterial infection. Using a mouse helminth-Salmonella co-infection system, we show that anthelmintic treatment prior to Salmonella challenge is sufficient to restore host resistance to Salmonella. The presence of the small intestine-dwelling helminth Heligmosomoides polygyrus at the point of Salmonella infection suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
(66 reference statements)
1
9
0
Order By: Relevance
“…Increasing evidence indicates that helminths alter the complex bacterial communities present within the intestine 14 , and that helminth-bacterial interactions result in alterations to the host immune responsiveness and can provide protection against inflammatory disorders 15 , 16 . Helminth infection can also alter host susceptibility to pathogen infection and a recent report demonstrates that the presence of an intestinal helminth at the time of Salmonella infection aids the establishment of Salmonella within the small intestinal lumen 17 . These findings indicate that disruption of one member of the intestinal ecosystem can have important implications on other members and/or on the host immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence indicates that helminths alter the complex bacterial communities present within the intestine 14 , and that helminth-bacterial interactions result in alterations to the host immune responsiveness and can provide protection against inflammatory disorders 15 , 16 . Helminth infection can also alter host susceptibility to pathogen infection and a recent report demonstrates that the presence of an intestinal helminth at the time of Salmonella infection aids the establishment of Salmonella within the small intestinal lumen 17 . These findings indicate that disruption of one member of the intestinal ecosystem can have important implications on other members and/or on the host immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, we have no direct evidence that intestinal tapeworm infection is this patient's primary cause of immunosuppression. Meanwhile, a recent study showed that removing worms after a Salmonella infection does not restore the host's resistance to Salmonella infection [18]. This study suggests that the immune response to bacterial pathogens did not recover rapidly in the period following deworming treatment.…”
Section: F I G U R E 1 Patient's Preoperative Computer Tomography Sca...mentioning
confidence: 90%
“…In experimental mouse models, the higher caecal abundance of Firmicutes and other genera of bacteria, but lower abundance of Parabacteroides and Prevotella in response to Trichuris muris infection (see Lawson et al 2021) were shown to limit T. muris egg hatching in the mouse gut, thus promoting a chronic T. muris infection by preventing reinfection, to the benefit of the parasite (White et al 2018). Expansion of Salmonella in the lumen of the mouse duodenum was limited following anthelmintic treatment of Heligmosomoides polygyrus (also referred to as H. p. bakeri and H. bakeri ), indicating that the presence of this intestinal nematode promotes expansion of Salmonella (Brosschot et al 2021). The impact of nematode infection on the host microbiome has also been shown to cross host generations.…”
Section: The Parasite Lensmentioning
confidence: 99%